Echoing Hooves: Studies on Horses and Their Effects on Medieval Societies
1 online resource.
Keywords: Saying that horses shaped the medieval world – and the way we see it today – is hardly an exaggeration. Why else do we imagine a medieval knight – or a nomadic warrior – on horseback? Why do we use such metaphors as “unbridled” or “bearing a yoke” in our daily language? Studies of medieval horses and horsemanship are increasingly popular, but they often focus on a single aspect of equestrianism or a single culture. In this book, you will find information about both elite and humble working equines, about the ideology and practicalities of medieval horsemanship across different countries, from Iceland to China. Contributors are Gloria Allaire, Luise Borek, Gail Brownrigg, Agnès Carayon, Gavina Cherchi, John C. Ford, Loïs Forster, Jürg Gassmann, Rebecca Henderson, Anna-Lena Lange, Romain Lefebvre, Rena Maguire, Ana Maria S. A. Rodrigues, and Alexia-Foteini Stamouli.